2017
DOI: 10.1007/s00394-017-1425-z
|View full text |Cite
|
Sign up to set email alerts
|

miR-124a expression contributes to the monophasic pattern of insulin secretion in islets from pregnant rats submitted to a low-protein diet

Abstract: Loss of biphasic insulin secretion in islets from LPP rats appears to have resulted from reduced [Ca] due, at least in part, to Kir6.2 underexpression and from the changes in exocytotic elements that are influenced either directly or indirectly by miR-124a.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…The expected biphasic secretion reported in normal pregnancy (Sorenson & Brelje, ) and observed in our control non‐pregnant pregnant rats was not verified in recovered and control pregnant rats. However, the pattern of insulin secretion exhibited by our control pregnant rats was also verified previously (de Siqueira et al., ). Interestingly, the kinetics of insulin secretion were not modified by pregnancy in the recovered and protein‐deficient groups.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The expected biphasic secretion reported in normal pregnancy (Sorenson & Brelje, ) and observed in our control non‐pregnant pregnant rats was not verified in recovered and control pregnant rats. However, the pattern of insulin secretion exhibited by our control pregnant rats was also verified previously (de Siqueira et al., ). Interestingly, the kinetics of insulin secretion were not modified by pregnancy in the recovered and protein‐deficient groups.…”
Section: Discussionsupporting
confidence: 91%
“…Short‐term protein restriction during pregnancy (from the first to the 15th day) produced higher basal insulin secretion, and the maximal insulin secretion was obtained in a physiological glucose range (Souza et al., ). This experimental model showed loss of biphasic insulin secretion that appeared to result from changes in exocytotic elements that are influenced either directly or indirectly by miR‐124a (de Siqueira et al., ). In contrast, in islets from pregnant rats that were subjected to prolonged protein restriction (from intrauterine life to adult life and pregnancy) there was reduced glucose responsiveness but similar glucose sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Although our results showed no damage in low-protein dams, it is known that a restriction of protein during pregnancy may induce changes in other pathways, such as glucoses metabolism and insulin secretion ( 37 , 38 ). A decrease in (Ca 2+ )i, as well as changes in gene expression in pancreatic islets ( 39 ) can explain the decreased insulin secretion in malnourished animals. A study also demonstrated that physical training before and during pregnancy attenuated the effects of a low-protein diet on the secretion of insulin ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…This effect may be partly explained by the increased β-cell and liver glucose transporter GLUT2 in the membrane of cultured neonatal rat islets. [25]…”
Section: Discussionmentioning
confidence: 99%